2014
DOI: 10.1016/j.ijdevneu.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin‐induced ventriculomegaly at weaning produces long‐term learning, memory, and motor deficits in rats

Abstract: Ventriculomegaly occurs when there is imbalance between creation and absorption of cerebrospinal fluid (CSF); even when treated, long-term behavioral changes occur. Kaolin injection in the cisterna magna of rats produces an obstruction of CSF outflow and models one type of hydrocephalus. Previous research with this model shows that neonatal onset has mixed effects on Morris water maze (MWM) and motoric performance; we hypothesized that this might be because the severity of ventricular enlargement was not taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…These cannot be attributed to difference in swimming ability between animals ( Figure 1B) (35,70). Our findings that hydrocephalus impaired rats' spatial learning and memory are consistent with earlier study testing the animals' performance with multiple day MWM task (15,70) as well. Our findings that hydrocephalus impaired rats' spatial learning and memory are consistent with earlier study testing the animals' performance with multiple day MWM task (15,70) as well.…”
Section: Functional Implication Of Hydrocephalusinduced Cortical and supporting
confidence: 92%
See 3 more Smart Citations
“…These cannot be attributed to difference in swimming ability between animals ( Figure 1B) (35,70). Our findings that hydrocephalus impaired rats' spatial learning and memory are consistent with earlier study testing the animals' performance with multiple day MWM task (15,70) as well. Our findings that hydrocephalus impaired rats' spatial learning and memory are consistent with earlier study testing the animals' performance with multiple day MWM task (15,70) as well.…”
Section: Functional Implication Of Hydrocephalusinduced Cortical and supporting
confidence: 92%
“…Like earlier studies, kaolin-induced hydrocephalic rats showed slower body weight gain (15,44,70). Acute hydrocephalic rats showed increased escape latency starting from the second trial block of the single-day MWM task while chronic animals (a different batch of animals, first exposure to the task) took longer to find the underwater platform than their age-matched controls starting in the first trail block of the day.…”
Section: Functional Implication Of Hydrocephalusinduced Cortical and supporting
confidence: 67%
See 2 more Smart Citations
“…Adapted from Williams et al 33 deficit persists using back-to-back phases, it would also remain for spaced phases. 34 Therefore, we think this is an appropriate way to monitor changes in learning and memory over time. For specific details, see Vorhees and Williams.…”
Section: The Second Advantage Of Swimming Tasks Is That 100%mentioning
confidence: 99%